Three-Dimensional Numerical Simulation of TsunamiBore Inundation Flow Around Cylindrical StructureSurrounded by Weir - Indradri Wijatmiko; Keisuke Murakami (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2012)
The extension of tsunami’s destruction due to the damaged of hazardous material containers, such as oil storage tanks, in the Japan tsunami 2011 leads to the investigation of tsunami inundation flow around cylindrical structure surrounded by weir. The investigations are conducted by using three-dimension numerical simulation based on modified Navier-Stoke equations and VOF model. Tsunami wave bore is introduced by applying an analytical equation, which proposed by Fukui (1962). The results indicate that the existence of protective weir significantly reduce wave velocity inside the protective weir.